UI/UX Design of Pratama Clinic Mobile Application Based on User Cultural Dimensions with User-Centered Design (UCD) Approach - Iqbal, Ahmad; Khudori, Ahsanun Naseh; Haris, M. Syauqi (Universitas Mohammad Husni Thamrin, 2025)
Digital transformation has brought significant changes to various sectors, including healthcare. Digital technology, particularly mobile applications, enables increased efficiency, accessibility, and service quality. In the context of digital healthcare, effective user interface (UI) and user experience (UX) design are key factors in increasing application adoption by users. This study aims to design a mobile application for Klinik Pratama using a User-Centered Design (UCD) approach and integrating local cultural values in Malang City to improve accessibility and user satisfaction. This study uses quantitative methods. Data collection techniques include in-depth interviews with respondents, participant observation, and prototype evaluation using the System Usability Scale (SUS). The cultural dimensions used include Power Distance, Collectivism, Uncertainty Avoidance, Masculinity vs. Femininity, and Long-Term Orientation, which are then implemented in UI design elements. The evaluation results show that the integration of UCD with a culture-based approach can significantly increase the application's usability value, with an average SUS score of 86.75 for patients, 87.5 for doctors, and 85.83 for administrative staff. All scores are included in the 'Good' category with a letter grade of 'B' based on the interpretation of the SUS standard. These findings confirm that a user-oriented design approach to culture can promote the inclusivity and effectiveness of primary digital health services through design strategies that are adaptive to local culture.